2011
DOI: 10.1111/j.1548-1433.2011.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Past in 2010

Abstract: In 2010, archaeologists investigated diverse, multilinear human histories and disagreed about what forces shaped these histories most powerfully. The varied new work covered in this review is organized into three broad themes. First, research on the relationship between people and environments included topics such as domestication and anthropogenic landscapes, social responses to environmental crisis, and adaptation. Second, archaeologists studying nonstate societies discussed the basis of inequality, the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 97 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Second, archaeologists are pushing what Liz called their archaeological imagination—finding new ways of asking questions that link the most empirical of research projects with innovative social theory. Although themes prevalent in 2010 (Arkush 2011a) continue to be salient in 2011, I noticed a shift in the discussion on agency from “something to look for” to “the ways in which people build arguments about it.” Debates played out about how we know what we know (or don't know) in archaeology. They ranged from calls for a renewed commitment to an empirical project where the field does not degenerate into scientific relativism (Demoule 2011) to those who have found interpretive potential in the possible multiplicities of ontologies that material culture can inhabit (Alberti, et al 2011).…”
mentioning
confidence: 99%
“…Second, archaeologists are pushing what Liz called their archaeological imagination—finding new ways of asking questions that link the most empirical of research projects with innovative social theory. Although themes prevalent in 2010 (Arkush 2011a) continue to be salient in 2011, I noticed a shift in the discussion on agency from “something to look for” to “the ways in which people build arguments about it.” Debates played out about how we know what we know (or don't know) in archaeology. They ranged from calls for a renewed commitment to an empirical project where the field does not degenerate into scientific relativism (Demoule 2011) to those who have found interpretive potential in the possible multiplicities of ontologies that material culture can inhabit (Alberti, et al 2011).…”
mentioning
confidence: 99%
“…Except for the Annales approach, history remains largely ignored in archaeology, whether it is history in terms of a way of understanding (Ribeiro 2018) or whether it is history in terms of methodological approaches. As pointed out by Elizabeth Arkush (2011) and Travis Stanton (2004), it seems archaeology can only follow two models of explanation -one which focuses exclusively on external constraints and another which focuses exclusively on human agency (Arkush 2011, Stanton 2004. Microhistory provides the basis in which both these elements intersect.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, there is the historical long-duration and medium-duration, which emphasize constraints in the form of environmental factors, structural forces, and long-term mentalities. On the other hand, there is the actor, who acts in the short-term and is contradictorily constrained and free at the same time (Arkush 2011;Stanton 2004). Braudel's historical project was designed to highlight all of these elements, but it seems clear that it has been unable to portray the agent as actually having any sort of agency -it has served only to emphasize the limitations of human action.…”
Section: Closing Commentmentioning
confidence: 99%
“…The focus by Andean archaeologists on mortuary practices that facilitated ongoing engagement with those dead recognized as ancestors is grounded in extensive and persuasive evidence. Yet the concept is so widely utilized that some scholars have cautioned that archaeologists must demonstrate rather than assume that ancestor veneration was salient and have suggested that our use of the term risks becoming so vague as to be rendered useless (Arkush ; Mantha ). Moreover, I note that to date there has been little consideration of how people in the pre‐Hispanic Andes conceptualized and responded to encounters with the dead of others.…”
Section: Andean Ancestorsmentioning
confidence: 99%